2021
DOI: 10.21203/rs.3.rs-1087508/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SCD1/FADS2 fatty acid desaturases equipoise lipid metabolic activity and redox-driven ferroptosis in ascites-derived ovarian cancer cells

Abstract: Malignant ascites in peritoneal metastases is a lipid-enriched microenvironment and is frequently involved in the poor prognosis of epithelial ovarian cancer (EOC). However, the detailed mechanisms underlying ovarian cancer (OvCa) cells dictating their lipid metabolic activities in promoting tumor progression remain elusive. Here, we report that two critical fatty acid desaturases, stearoyl-CoA desaturase-1 (SCD1) and acyl-CoA 6-desaturase (FADS2), are aberrantly upregulated, accelerating lipid metabolic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…When SCD1/FADS2 is inhibited, its iron-binding capacity declines, leading to an accumulation of cellular iron. Experiments also revealed that inhibition of SCD1/FADS2 activities led to an increase in Fe 2+ levels, which in turn resulted in ROS buildup and lipid peroxidation [42].…”
Section: Stearoyl Coa Desaturase 1 (Scd1) Induces Ferroptosismentioning
confidence: 97%
See 2 more Smart Citations
“…When SCD1/FADS2 is inhibited, its iron-binding capacity declines, leading to an accumulation of cellular iron. Experiments also revealed that inhibition of SCD1/FADS2 activities led to an increase in Fe 2+ levels, which in turn resulted in ROS buildup and lipid peroxidation [42].…”
Section: Stearoyl Coa Desaturase 1 (Scd1) Induces Ferroptosismentioning
confidence: 97%
“…Xuan et al [42] reported a novel cellular antioxidant system that SCD1/FADS2 could regulate GPX4 and the GSH/GSSG ratio to prevent excess ROS-mediated oxidative stress and ferroptosis. SCD1/FADS2 are the key iron-containing enzymes whose enzymatic activities are executed by binding to iron [43].…”
Section: Stearoyl Coa Desaturase 1 (Scd1) Induces Ferroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…To con rm the contribution of lipid accumulation on the polarization of protumoral TAMs 39 , FACS analysis using the lipophilic uorescent dye BODIPY 493/503 showed that PBMC MΦs cultured in OCM or ascites uid (AS) displayed a signi cantly higher level of lipid accumulation. Our previous report has mentioned that unsaturated fatty acids (UFAs) are remarkably upregulated in the malignant ascites of EOC patients with peritoneal metastases 21,22 . The lipidomic analysis further revealed that unsaturated fatty acids such as linoleic acid (C18:2, LA) are abundant in MAM 21,22 .…”
Section: Mam Reinforces Lipid Metabolic Activities In Protumoral Tamsmentioning
confidence: 99%
“…These results indicate that PUFAs are a key player in promoting tumor-in ltrated TAMs polarization that, in turn, facilitates EOC tumor growth and metastasis.Clinical evidence has revealed that epithelial ovarian cancer (EOC) possesses precedential metastatic tropism for the adipose-enriched omentum and accumulation in ascites, suggesting that the lipidenriched tumor microenvironment (TME) plays a pivotal role in facilitating tumor progression and metastasis 3,19,20 . Recent evidence suggests lipid-enriched TME fuels tumor cells and exacerbates EOC progression through lipid metabolic reprogramming 21,22,23 . Simultaneously, lipid-enriched TME affects in ltrated immune cell differentiation and antitumor activity, and maintaining a suppressive immune microenvironment facilitates tumor progression 24,25, 26 .…”
mentioning
confidence: 99%